Measuring User Satisfaction of iPusnas Through the End-User Computing Satisfaction Model - Khoirunisa Jannatuzzahra; Arista Pratama; Asif Faroqi (bit-Tech, 2025)
iPusnas serves as Indonesia’s national digital library platform, offering free access to electronic books for the general public. This research aims to evaluate user satisfaction with the iPusnas application by employing the End-User Computing Satifactions (EUCS) model, which comprises five main constructs: content, acuracy, format, ease of use, and timelines, along with two additional dimensions—system speed and system reliability. The study involved 450 participants selected through purposive sampling. Data analysis was conducted using the Partial Least Squares Structural Equations Modeling (PLS-SEM) technique with the assistance of SmartPLS 4 software. The findings indicate that six variables—content, ease of use, format, accuracy, system speed, and system reliability—have a statistically significant and positive impact on user satisfaction. This suggests that a higher level of perceived quality in these six areas corresponds to greater satisfaction among users. On the other hand, timeliness was found to have a significant yet negative influence. These results suggest that delays in delivering content or in system responsiveness remain key issues that negatively affect user experience. Accordingly, this study recommends enhancing system performance, particularly in terms of timeliness to improve user satisfaction and the overall experience. Strengthening these areas is also anticipated to contribute to increased user engagement and further the national objective of expanding digital literacy and equitable knowledge access across the country.